1986
DOI: 10.1177/000456328602300406
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Insulin-Like Growth Factor I: Clinical Applications and Significance

Abstract: Of the somatomedins so far measured, the selective quantitation of insulin-like growth factor I (IGF-I) appears to have the greatest potential in clinical diagnosis. There have been two approaches to the development of immunoassay systems. One type uses antibodies raised against synthetic fragments of IGF-I which exhibit cross-reactivity with the whole hormone. Such assay systems may be adequate for measuring normal adult plasma IGF-I levels, but the potential for the higher sensitivity required for detecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 61 publications
3
22
0
1
Order By: Relevance
“…Thereafter, plasma IGF-I declines steadily until normal adult values are reached (12,25). After 40 y of age, IGF-I declines again to levels lower than in early adulthood (26).…”
Section: Discussion Table 4 Correlation Of Individual Concentrationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Thereafter, plasma IGF-I declines steadily until normal adult values are reached (12,25). After 40 y of age, IGF-I declines again to levels lower than in early adulthood (26).…”
Section: Discussion Table 4 Correlation Of Individual Concentrationsmentioning
confidence: 97%
“…The pattern of IGF-I development from childhood to adult life has been more consistently established (8,12,26). Although the methodologies are still evolving, the plasma IGF-I concentration typically increases with age in young children (>10.3 nM or 80 /Lg/L) with a prominent surge (>51 nM or 400 /LgIL) at puberty (20,27).…”
Section: Discussion Table 4 Correlation Of Individual Concentrationsmentioning
confidence: 99%
“…We postulated that the discrepancies observed in the circulating levels of GH and IGF-I in the combination group can be explained by the fact that stimuli other than GH, such as prolactin (PRL), platelet-derived growth factor, or nutritional status, can also lead to an increase in IGF-I synthesis (30,31). Dardenne et al (32) reported that cells expressing GH receptor also express receptors for PRL.…”
Section: Discussionmentioning
confidence: 99%
“…Samples of medium and patients' serum underwent acid ethanol extraction with 2 N hydrochloric acid: absolute ethanol, 1:7 and were neutralised with Tris buffer. Duplicate aliquots were assayed using anti-IGF-I monoclonal antibody BPL-M23 as previously described (Teale & Marks, 1986;. Analysis of variance and Dunnett's test were used to assess the significance of differences in NSE and IGF-I levels before and during octreotide therapy.…”
Section: Growth Assaysmentioning
confidence: 99%